The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1001/archinte.161.10.1261
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Explicit Financial Incentives on Physician Behavior

Abstract: Managed care organizations use explicit financial incentives to influence physicians' use of resources. This has contributed to concerns regarding conflicts of interest for physicians and adverse effects on the quality of patient care. In light of recent publicized legislative and legal battles about this issue, we reviewed the literature and analyzed studies that examine the effect of these explicit financial incentives on the behavior of physicians. The method used to undertake the literature review followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 14 publications
0
96
0
4
Order By: Relevance
“…28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs. 24,[30][31][32][33][34] Studies of Ontario's pay-forperformance initiatives showed modest improvements in delivery of some preventive services 35,36 and no change in management of patients with diabetes. 37 The Ontario picture is complicated by the fact that physician payment mechanisms were also modified, which may have influenced both care for patients with chronic disease 38 and uptake of incentives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs. 24,[30][31][32][33][34] Studies of Ontario's pay-forperformance initiatives showed modest improvements in delivery of some preventive services 35,36 and no change in management of patients with diabetes. 37 The Ontario picture is complicated by the fact that physician payment mechanisms were also modified, which may have influenced both care for patients with chronic disease 38 and uptake of incentives.…”
Section: Discussionmentioning
confidence: 99%
“…39 Most research in this area focuses on care for individual diseases, using the delivery of specific services as indicators of quality. 24,[30][31][32][33][34] Evidence of the effect of incentive-based programs on broader outcomes such as access to primary care, continuity of care, 40 hospital admissions [25][26][27][28][29]41,42 and overall resource use 30,34,43 has been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…2 There is some evidence that the size of the incentive must be large enough to achieve behaviour response. [13][14][15][16][17][18][19] One study surveyed managers of health management organizations in the United States about how primary care physicians responded to financial incentives, and showed that bonuses of at least 5% of income would be sufficient to achieve behaviour change. 15 Other research has identified several factors influencing the impact of pay for performance, including incentive size, duration, group versus individual incentives and case-mix risk-adjustment techniques.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although pay for performance has been widely implemented, there is equivocal and limited evidence regarding its effectiveness. 19,[22][23][24][25][26][27] A systematic review of the effect of financial incentives for primary care physicians found modest or no effects. 23 Lavergne and colleagues 4 evaluated pay-for-performance payments for primary care physicians in BC and found that incentives had no effect on visits or continuity of care, but were associated with increased rates of hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…Health services research does little to resolve the debate: The literature on the impact of financial incentives on physician behavior is rather thin. 6 Regardless of their true impact on quality, plan managers believe that the programs are popular with providers (especially if there are only winners and no losers). Even so, most plan officials consider them a luxury that is feasible only in good financial times.…”
Section: Gathering Information: Profiling the Physician Networkmentioning
confidence: 99%